Community Potential Empowerment: Participatory Action Research in Sungai Durian Village Lamposi Tigo Nagari Payakumbuh - Cahyananda Dwi Putri; Rozaanah Rozaanah; Annisa Salsabilla Albarad; Aulia Rahmah; Leginta Puti Sakinah; Putri Nurhalimah; Salsa Ikhlasiyah; Siti Sarah (ASSUNNAH PRESS, 2023)
The STAI As-sunnah Deli Serdang service activities occur in Sungai Durian Village Lamposi Tigo Nagari Payakumbuh. This place was chosen for several reasons, including the request of several community leaders who are also student guardians and already know STAI As-Sunnah as an educational forum that produces teachers who have proven Arabic language competence. Based on this, Sungai Durian residents hope that the activities carried out in their area are able to give a new colour to the younger generation so that they are interested in continuing their studies at STAI As-Sunnah. The students, as researchers, used the Participatory Action Research (PAR) approach aimed at empowering the potential in the local community and helping the community by starting from the problems and needs of the local community. With this approach, it is hoped that there will be the development of community potential and solving problems local communities face. Several program activities were carried out at one of the masjids and one of the informal community institutions, the Medina Quran House, as a community forum for learning tahsin and memorizing the Al-Qur’an. The data collection technique was obtained through direct field observations and interviews. The data obtained were analyzed descriptively and presented in tabular form. Through the programs carried out, data is obtained that shows changes in a positive direction toward the problems being faced by the community. The methods and techniques researchers use include applying the Jibril method for learning tahsin and tahfiz of the Al-Qur’an, using animated film media for learning Arabic, distributing free takjil, and cultivating quails received a positive response from the local community. The programs implemented aim to serve social services for the community.